MANAGEMENT OF EMPHYSEMATOUS PYELONEPHRITIS – A CLINICAL CASE - V. Dulgerov; T. Ganev; A. Vasileva; M. Nankova; K. Eguruze (Trakia Journal of Sciences)
Emphysematous pyelonephritis is a rare, serious gas-forming infection of the renal parenchyma and surrounding tissues. Radiological classification and adequate therapeutic regimen are controversial, and prognostic factors and pathogenesis remain uncertain. The aim of the research is to present the management of emphysematous pyelonephritis in a woman with newly diagnosed diabetes. The clinical case presents a 68-year-old female patient admitted to the internal ward in a seriously damaged general condition- difficult to communicate, inadequate, in deep sopor, with severe febrileintoxication, astheno-adynamic, upper- and lower-dyspeptic syndromes. With a negative test for COVID-19 upon admission, other tests from the emergency department showed hyperglycemia, ketoacidosis, slightly increased values of nitrogen bodies in the blood, significantly increased values of osteophase inflammatory markers, rich urine findings.The results of computer-axial tomography of the abdomen, performed the day after admission, with evidence of emphysematous pyelonephritis on the right, with distended intestinal loops along the course of the large intestine, without free air in the abdominal cavity. The clinical picture and therapeutic behavior, as well as the outcome of the disease, were followed and described in the woman with emphysematous pyelonephritis and newly diagnosed diabetes. Material and methods: clinical observation, analysis of medical documentation and literature sources Discussion: Emphysematous pyelonephritis usually affects elderly patients, mostly women. A particularly favorable for development is observed among patients with diabetes and obstruction of the urinary tract. The main causative agent is Escherichia coli. Computed axial tomography is the key to diagnosis. Treatment requires a combination of intensive care with appropriate antibiotics and frequent drainage of the affected kidney. Nephrectomy may be required from the beginning or after drainage failure.